Screen time and early childhood development in Ceará, Brazil: a population-based study - Hermano Alexandre Lima Rocha; Luciano Lima Correia; Álvaro Jorge Madeiro Leite; Márcia Maria Tavares Machado; Ana Cristina Lindsay; Sabrina Gabriele Maia Oliveira Rocha; Jocileide Sales Campos; Anamaria Cavalcante e Silva; Christopher Robert Sudfeld (BMC, 2021)
Abstract Background Globally, children's exposure to digital screens continues to increase and is associated with adverse effects on child health. We aimed to evaluate the association of screen exposure with child communication, gross-motor, fine-motor, problem-solving, and personal-social development scores. Methods We conducted a population-based, cross-sectional study with cluster sampling among children 0-60 months of age living in the state of Ceará, Brazil. Child screen time was assessed by maternal report and the World Health Organization (WHO) recommendations were used to define excessive screen time exposure. Child development was assessed with the Brazilian Ages and Stages Questionnaire. Generalized linear regression was used to determine the association of screen exposure with developmental outcomes. We also examined the potential non-linear relationship of screen time with development scores using spline analyses. Results A total of 3155 children 0-60 months of age had screen time exposure evaluated and 69% percent were identified as exposed to excessive screen time. This percentage of excess screen time increased with child age from 41.7% for children 0-12 months to 85.2% for children 49-60 months. Each additional hour of screen time was associated with lower child communication (standardized mean difference (SMD): -0.03; 95% CI: − 0.04, − 0.02), problem solving (SMD: -0.03; 95% CI: − 0.05, − 0.02) and personal-social (SMD: -0.04; 95% CI: − 0.06, − 0.03) domain scores. Conclusions Excess screen time exposure was highly prevalent and independently associated with poorer development outcomes among children under 5 years of age in Ceará, Brazil.